2020
DOI: 10.1177/1046878120953453
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Educational Escape-Room Success: The Process of Designing, Piloting, Evaluating, Redesigning, and Re-Evaluating Educational Escape Rooms

Abstract: Background. The implementation of educational escape rooms has shown great value in learner outcomes. The design of such simulations requires a thoughtful, well-defined process. Objective. The purpose of this article is to encourage educational escape room designers to use a thoughtful, methodical, iterative process to ensure quality, educational capacity, and a positive learner experience. Application. When designing an educational escape room, designers should consider implementing a cyclic design process: d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…This underlines the importance of testing linking clues and preventing early reveals of clues. 35 , 36 Additional lockboxes with associated clues and puzzles resolved these issues.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the importance of testing linking clues and preventing early reveals of clues. 35 , 36 Additional lockboxes with associated clues and puzzles resolved these issues.…”
Section: Discussionmentioning
confidence: 99%
“…As we highlighted, and this is emphasized by Anderson et al (2020) and Eukel and Morrell (2020) a logical next step for many escape rooms is assessing the impact of these unique strategies. Some authors (Frederick & Reed, 2020; Hardie, et al 2020; McLaughlin, et al, 2020) conducted pilot study research and found some positive results.…”
mentioning
confidence: 98%
“…As implied earlier in this editorial, the intent of the articles in this symposium is to encourage and guide further application and testing of escape rooms as a teaching strategy for multiple disciplines. In their article, Eukel and Morrell (2020) provide a starting point for creating, piloting, and evaluating new content being delivered in this fashion. Readers will find this article useful for operationalizing ideas, while following best practices in the delivery of an escape room, which can be applied to all disciplines.…”
mentioning
confidence: 99%
“…For the design of educational escape rooms, available models comprise step-by-step procedures (Botturi, & Babazadeh, 2020;Clarke et al, 2016;Eukel, & Morrell, 2020;Guigon, Humeau, & Vermeulen, 2018). However, these models do not take into account design challenges for educational games, as described in the previous section.…”
Section: Discussionmentioning
confidence: 99%
“…Students were more active and collaborative when the used puzzle organisation created positive social interdependence. For the design of educational escape rooms, the available models comprise step-by-step procedures (Botturi & Babazadeh, 2020;Eukel, & Morrell, 2020;Guigon et al, 2018). However, design challenges for educational games are not considered.…”
Section: Theoretical Grounding Of Educational Escape Roomsmentioning
confidence: 99%